2002
DOI: 10.1117/12.484491
|View full text |Cite
|
Sign up to set email alerts
|

<title>New developments of optopolarization sensor devices and articles based on them</title>

Abstract: Polarization methods are widely used in studies of different physical, chemical and geometrical characteristics of objects. The spectrum of such methods application is wide enough. The results, received using these methods allow to measure the phase characteristics of wavelength with the accuracy of iO X.The basic tendency of these methods development and modernization is aimed at the miniaturization of the polarization measuring means. The optical polarization sensors that are developed and produced at the Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The concept involves the formation of the effective spatial structure of the country's economy while respecting the balance of interests of all subjects of the Russian Federation (Sycheva et al, 2017;Voronkova et al, 2018;Telyakov et al, 2016;Ivanova et al, 2018). The analysis of the presented concept shown that considered attention is paid to the regional aspect, justified the possibility of transition to sustainable development of the Russian Federation under the condition of sustainable development of its territories (Fedorinin and Zhuravlev, 2002;Nechaev et al, 2018a,b). We believe that this is possible only in the formation of an effective spatial structure of the country's economy and the balance of interests of all subjects of the Russian Federation.…”
Section: Resultsmentioning
confidence: 89%
“…The concept involves the formation of the effective spatial structure of the country's economy while respecting the balance of interests of all subjects of the Russian Federation (Sycheva et al, 2017;Voronkova et al, 2018;Telyakov et al, 2016;Ivanova et al, 2018). The analysis of the presented concept shown that considered attention is paid to the regional aspect, justified the possibility of transition to sustainable development of the Russian Federation under the condition of sustainable development of its territories (Fedorinin and Zhuravlev, 2002;Nechaev et al, 2018a,b). We believe that this is possible only in the formation of an effective spatial structure of the country's economy and the balance of interests of all subjects of the Russian Federation.…”
Section: Resultsmentioning
confidence: 89%
“…In the authors' opinion, a rural territory should be considered as a territory of agricultural activity with the presence of the rural population, as well as social infrastructure objects that need to be developed as a combination of social relations and institutional entities (Dashko and Kotiukov, 2017;Fedorinin and Zhuravlev, 2002;Yemelyanov et al, 2018a;2018c;Zagrivnyi et al, 2019;Yemelyanov et al, 2019). It is worth noting that the current level of socio-economic development of rural areas does not meet the interests of the rural population and does not provide a decent quality of life for the rural populationcarriers of the human capital of rural areas (Nechaev et al, 2018;Stoian et al, 2018;Sharafutdinov et al, 2017;Dmitrieva et al, 2017;Ponomareva et al, 2019a,b;Leonteva et al, 2018;Johnson and Hinton, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the symbiosis of definitions of "sustainable development" is interpreted as a constant change and continuous improvement (today is better than yesterday, and tomorrow is better than today). In this regard, sustainable development should be considered as a basis in territorial management strategies (Pavlyuk et al, 2018;Voronkova et al, 2019;Prodanova et al, 2019a;Goloshchapova et al, 2018;Fedorinin and Zhuravlev, 2002;Ivanova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%